REFORMULASI SANKSI PIDANA TERHADAP PERUSAHAAN YANG TIDAK MELAKUKAN PENERAPAN TERHADAP KESELAMATAN DAN KESEHATAN KERJA - Safrianda Safrianda; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In Indonesia the implementation of occupational safety and healthregulations is regulated in Law No. 1 of 1970 concerning Occupational Safety andHealth, with the aim of providing protection to workers or laborers in carrying outtheir work in the work environment. However, in this Law, companies that violatethe provisions of this Law can be given very light criminal sanctions and do notprovide justice if applied at this time. Therefore, a renewal of criminal law isneeded to increase the number of criminal sanctions with the aim of providing adeterrent and justice effect for workers or laborers and to provide protection forworkers or laborers in the future. The purpose of this thesis, namely; First, todetermine the arrangements for the protection of occupational safety and healthfor workers or laborers in the perspective of Law No. 1 of 1970. Second: To findout how to reform criminal sanctions against companies that do not apply tooccupational safety and health.This type of research can be classified in the type of normative legalresearch, because in this study the authors conducted research by examininglibrary materials. The data sources used are, secondary data consisting of primarylegal materials, secondary legal materials, and tertiary legal materials, because theauthors conducted research on legal principles by utilizing deskrptive methods toprovide an overview of overcoming violations of occupational safety and health,with the purpose of providing protection for workers or workers from workrelatedaccidents.From the results of the study it can be concluded, First: The regulation ofthe protection of occupational safety and health for workers or laborers in LawNumber 1 Year 1970 concerning Occupational Safety and Health is still lacking,namely criminal sanctions given are still very light and do not provide a deterrenteffect and taste justice. Second: it requires renewal or reformulation of criminalsanctions by adding the number of imprisonment sanctions or criminal penalties.In the hope of giving a deterrent effect and a sense of justice. In the hope ofreformulating more stringent criminal sanctions, so that companies carry out goodwork safety and health programs, so that workers are protected from the dangersof workplace accidents.Keywords: Reformulation-workers-work safety